2022
DOI: 10.3390/biom12111625
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis: A Newly Discovered Therapeutic Target for Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion (I/R) injury, uncommon among patients suffering from myocardial infarction, stroke, or acute kidney injury, can result in cell death and organ dysfunction. Previous studies have shown that different types of cell death, including apoptosis, necrosis, and autophagy, can occur during I/R injury. Pyroptosis, which is characterized by cell membrane pore formation, pro-inflammatory cytokine release, and cell burst, and which differentiates itself from apoptosis and necroptosis, has been found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 123 publications
3
6
0
1
Order By: Relevance
“…Notably, enhanced pyroptosis promotes the development of MI/RI, so many studies have been devoted to identifying drugs that inhibit pyroptosis or the underlying molecular mechanism. [43,44] In the present study, our results demonstrated that the injury. [41] There were multiple reasons for the opposite results.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Notably, enhanced pyroptosis promotes the development of MI/RI, so many studies have been devoted to identifying drugs that inhibit pyroptosis or the underlying molecular mechanism. [43,44] In the present study, our results demonstrated that the injury. [41] There were multiple reasons for the opposite results.…”
Section: Discussionsupporting
confidence: 73%
“…Notably, enhanced pyroptosis promotes the development of MI/RI, so many studies have been devoted to identifying drugs that inhibit pyroptosis or the underlying molecular mechanism. [ 43,44 ] In the present study, our results demonstrated that the promotion of pyroptosis in rats with MI/RI and in cardiomyocytes induced by H/R was attenuated by ALKBH5 knockdown. Taken together, these findings led us to propose that ALKBH5 knockdown weakens pyroptosis to alleviate MI/RI.…”
Section: Discussionsupporting
confidence: 63%
“…Pyroptosis is an inflammatory form of regulated cell death characterized by the activation of proinflammatory caspases and the formation of plasma membrane pores, which eventually leads to cell lysis [ 16 , 22 ]. Previous studies have shown that pyroptosis mediates a variety of downstream effects by activating caspase-1 through the canonical pathway or caspase-4/5/11 through the noncanonical pathway [ 9 ]. In both pathways, gasdermin D (GSDMD) is the key effector of pyroptosis initiation.…”
Section: Programmed Cell Death In Iri-akimentioning
confidence: 99%
“…Previous studies have suggested that tubular cell death by necrosis and apoptosis is the major mechanism associated with renal IRI [ 8 ]. However, recent research has challenged traditional views of cell death by identifying new pathways in which cells die in a regulated manner, including pyroptosis [ 9 ], necroptosis, and ferroptosis [ 10 ]. In this review, we summarize the current status of research on the molecular mechanisms and pathways of AKI induced by IRI.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, in response to harmful stimuli, toll-like receptors (TLRs) of multiple cells activate assembly of multiple-protein complexes and NLR family pyrin domain containing 3 (NLRP3)- inflammasome, which induce the activation and maturation of caspase-1, leading to the proteolytic maturation of the pro-inflammatory cytokines Interleukin(IL)-1β and IL-18, as well as the pore-forming protein GSDMD, and the resulting N-terminal fragment (GSDMD-N) then undergoes a conformational change, oligomerizes, and binds to the cell membrane which forms pyroptotic pores on the surface of cell membrane and therefore actives release of mature proinflammatory cytokines such as IL-1β and IL-18 [ 12 , 13 ]. It should be noticed that studies have suggested tubular pyroptosis contributed to severe AKI [ 14 16 ]. The earliest study in 2014 found that renal I/R injury induce the pyroptosis of renal tubule epithelial cells via the CHOP-caspase-11 pathway [ 17 ].…”
Section: Introductionmentioning
confidence: 99%